Improving large taxpayers' compliance : a review of country experience - Baer, Katherine; Toro, Juan.; Benon, Olivier; International Monetary Fund. (Washington, DC : International Monetary Fund, 2002)
This book provides an overview of the organisation, systems, and procedures used by tax administrations in about 40 countries to monitor the compliance of the large taxpayers.
Includes bibliographical references (p. 57).
"Staff team led by Katherine Baer and comprising Olivier Benon and Juan Toro"--p. vii.
aug 3/06/13
Loans.
Keywords: Taxpayer compliance -- Developing countries; Tax administration and procedure -- Developing countries; Tax administration and procedure; Taxpayer compliance